Моделювання надійності збірних інструментів для важких токарних верстатів - Клименко, Галина Петрівна; Васильченко, Яна Василівна (Національний технічний університет "Харківський політехнічний інститут", 2020)
В роботі вирішена задача підвищення надійності збірних інструментів для важких токарних верстатів. Наголошено, що при експлуатації важких верстатів простої потребують великих коштів, значно знижують якість процесу експлуатації технологічної системи. Метою статті є підвищення якості процесу експлуатації технологічної системи обробки деталей шляхом розробки математичних моделей для прогнозування надійності збірних інструментів. Доведено перевагу комплексного показника надійності інструменту – коефіцієнта готовності. Збірні різці розглядаються як послідовна система з точки зору їх надійності. Представлено систему показників надійності різального інструменту. Застосовуючи марківський підхід до опису системи і припущення експоненційного розподілу часу роботи і відновлення інструменту, розроблено математичні моделі коефіцієнтів готовності збірних різців.

The problem of increasing the reliability of prefabricated tools for heavy lathes is solved in the work. The idea of implementing ISO 9000 series standards is justified. The need to develop a quality system for the machining process has been proven. Qualimetric indicators of quality of machines, cutting tools and processes of ensuring their trouble-free operation are defined. The aim of the article is to improve the quality of operation of the technological system of processing parts by developing mathematical models for predicting the reliability of assembly tools. Special attention is paid to the operation of cutting tools for heavy machines. The high cost of such tools is emphasized. Attention to reducing downtime of heavy machines is paid. The statistical analysis of indicators of operation of assembly cutting tools is carried out. It is proved that tool failure is one of the significant factors of machine downtime. The system of indicators of reliability of the cutting tool is presented. The reliability of the assembled tools for heavy machines is considered. The operation of the machine during operation is analyzed. Two ways to restore the efficiency of the tools are analyzed. State 0, when the machine is operational, and state 1, when the machine is idle are considered. Markov's approach to the description of the system is applied. Assumptions about the exponential distribution of operating time and tool recovery are made. The advantage of a complex indicator of tool reliability - readiness factor is proved. Assembly tools are considered as a consistent system in terms of their reliability. The number of system elements depends on the design of the tool. Mathematical models of readiness coefficients for two designs of assembly cutters are developed. The effectiveness of the use of research results proved. The distribution of reliability between the structural elements is determined at the design stage of the tool. The quality of the technological system is determined at the stage of its operation. Design solutions must be chosen to ensure serviceability. This will provide a given level of reliability.
Modeling the reliability of assembly tools for heavy lathes
Keywords: системний підхід; працездатність; інтенсивність відмов; system approach; efficiency; failure rate